Calcium pyrophosphate deposition (CPPD) disease – Treatment options. Issue 4 (December 2021) - Stack, John; McCarthy, Geraldine
Abstract: In contrast to gout, no disease-modifying therapies currently exist that reduce articular crystal deposition of calcium pyrophosphate crystals (CPPs). Treatment is aimed at ameliorating the inflammatory response and reducing the frequency and severity of clinical symptoms due to CPP deposition (CPPD). Despite being one of the most common forms of inflammatory arthritis, CPPD remains under-studied and evidence-based treatment guidelines remain lacking. Commonly used treatments for clinical manifestations of CPPD (non-steroidal anti-inflammatory drugs [NSAIDs], colchicine and corticosteroids [CSs]) are extrapolated from use in gout. Anakinra and tocilizumab can be used in refractory cases. Though no current crystal-targeted treatments exist, studies suggest that nucleoside analogues and phosphocitrate can attenuate calcification of human cartilage ex-vivo . Hindering research, is the lack of a well-defined description of CPPD. However, international working groups have convened to establish classification criteria and validated outcome domains for CPPD. This should help facilitate the setting up of large multicentre studies, with well-defined cohorts, which can evaluate suitable therapies, providing high levels of evidence to guide clinicians. Here, we summarise and discuss the currently available anti-inflammatory treatment options for CPPD and discuss potential future crystal-targeted approaches.